Green energy investment, renewable energy consumption, and carbon neutrality in China - Li, Ying; Li, Haoning; Chang, Manru; Qiu, Shijuan; Fan, Yifan; Razzaq, Hafiz Kashif; Sun, Yunpeng (Frontiers in Environmental Science, 2022)
The study investigates the dynamic impact of green energy investment and energy consumption on carbon emissions in China using the monthly data from M1-1995 to M12-2021. The study employed the Bootstrap Autoregressive Distributed Lag method to examine the short and long-run relationship. The study findings indicate that green energy investment and renewable energy consumption decrease carbon emissions, whereas non-renewable energy consumption and economic growth increase carbon emissions in shorter and longer periods. However, the marginal contribution of renewable energy towards carbon neutrality is significantly higher compared to green energy investment due to investment lag effects. Moreover, the Error Correction Term (ECT) is significantly negative, authorizing the convergence towards steady state equilibrium in case of any deviation with 25% adjustment rate. The empirical results suggest that China should encourage green energy investment and increase the share of renewable energy sources to ensure carbon neutrality in the long run.